The Effect of Climate on Residential Electrical Energy Consumption in Jeddah City - Samili, Khadija Muhammad; Boqri, Faida Kamel (Journal of Humanities & Social Sciences, 2024)
This scientific paper focuses on assessing the impact of climate on residential electricity consumption in Jeddah city, where residential electricity consumption rates vary according to cooling and heating needs throughout the year. The study aimed to raise awareness among households about natural variables and their impact on human activity, as well as to enhance the role of the Kingdom of Saudi Arabia in its efforts to increase housing energy efficiency and sustainability regarding climate effects. To achieve the study's goal, a descriptive-analytical approach was used to describe and detail the study variables over the period (2006-2020 AD), followed by data analysis, correlation, and statistical analysis to derive results that helped in elucidating solutions and recommendations serving the study's objective. The study demonstrated that: 1) residential electricity consumption rates vary throughout the year in Jeddah city, peaking in September and declining in February, 2) there is a strong negative correlation between temperatures and residential electricity consumption during the year, 3) temperatures, relative humidity, and wind speed affect residential electricity consumption in Jeddah city, especially temperatures. Thus, the results highlight the significant impact of climatic factors on residential electricity in Jeddah city, recommending the development of sustainable housing practices such as natural landscaping, avoiding artificial trees, utilizing alternative energies like solar power, and mandating the purchase of energy-efficient electrical appliances to reduce residential electricity bills.
Keywords: Applied Climate; Residential Electricity Consumption; Temperature; Relative Humidity; wind speed